A comparative study of different contrast administration routes efficiency performed on in vivo colorectal cancer models - A. S. Goncharova; D. V. Khodakova; A. V. Galina; A. V. Zaikina; L. Z. Kurbanova; M. V. Mindar; S. V. Gurova (Исследования и практика в медицине, 2022)
Purpose of the study. The investigation is aimed to provide a systematic comparison of different contrasting methods for in vivo micro-CT diagnostic of orthotopic colorectal cancer models extracted by ortotopic implantation into the caecum of immunocompromised mice BALB/c Nude lines.Materials and methods. BALB/c Nude (N = 25) female mice were implanted by transplanted human colorectal cancer strain into the cecum. 20 days after the implantation mice were administered with iodine-based contrast agent Optiray by means of different administration method (intravenously, per os, intraperitoneally, per rectum) and micro-CT scans have been registered via Quantum GX2 tomograph. Measurement of tumor nodes was performed both by means of estimation from micro-CT images via RadiAnt DICOM Viewer software and by means of explicit measurements using calipers upon laparotomy and posthumously. At the last stage of the study, the animals were euthanized by cervical dislocation. The tumors were excised, measured with a caliper and placed in 10 % formalin for the standard histological analysis according to the standard methods.Results. The average volumes of tumor xenografts in animals with intravenous, oral, and intraperitoneal contrast administration measured at micro-CT were 53.7 ± 5.2 mm3, 52.7 ± 6.4 mm3 and 63.6 ± 5.6 mm3 respectively; measured at laparotomy – 43.0 ± 5.5 mm3, 44.5 ± 5.4 mm3 and 58.5 ± 5.5 mm3 respectively; measured post-mortem – 55.2 ± 6.6 mm3, 53.2 ± 8.8 mm3 and 65.9 ± 3.8 mm3 respectively. The average volumes of tumor xenografts isolated post-mortem in these groups were comparable with the values shown at micro-CT, but larger than the volumes measured at laparotomy.Conclusion. The results obtained demonstrated that intravenous, peroral and intraperitoneal administration techniques provide the best visualization of laboratory rodents pathological tissue upon in vivo micro-CT diagnostics and thus are preferred.